Alpha‐thalassemia intellectual disability: variable phenotypic expression among males with a recurrent nonsense mutation – c.109C>T (p.R37X). (30th May 2014) - Basehore, M.J.; Michaelson‐Cohen, R.; Levy‐Lahad, E.; Sismani, C.; Bird, L.M.; Friez, M.J.; Walsh, T.; Abidi, F.; Holloway, L.; Skinner, C.; McGee, S.; Alexandrou, A.; et al.
<x xml:space="preserve">Abstract</x> Alpha‐thalassemia intellectual disability, one of the recognizable X‐linked disability syndromes, is characterized by short stature, microcephaly, distinctive facies, hypotonic appearance, cardiac and genital anomalies, and marked skewing of X‐inactivation in female carriers. With the advent of next generation sequencing, mutations have been identified that result in less severe phenotypes lacking one or more of these phenotypic manifestations. Here we report five unrelated kindreds in which a c.109C>T (p.R37X) mutation segregates with a variable but overall milder phenotype. The distinctive facial appearance of alpha‐thalassemia intellectual disability was present in only one of the 18 affected males evaluated beyond the age of puberty, although suggestive facial appearance was present in several during infancy or early childhood. Although the responsible genetic alteration is a nonsense mutation in exon 2 of ATRX, the phenotype appears to be partially rescued by the production of alternative transcripts and/or other molecular mechanisms.